Fumigant Toxicity of the Essential Oils from Medicinal Plants Against Bean Weevil, Acanthoscelides obtectus (Say) (Coleoptera: Bruchidae) - Sertkaya, Erdal (Asian Journal of Chemistry, 2012)
Fumigant activity of essential oil vapours from the aromatic plants such as, wild thyme (Thymus serpyllum L., Lamiaceae), origanum (Origanum onites L., Lamiaceae), rosemary (Rosmarinus officinalis L, Lamiaceae), basil (Ocimum basilicum L., Lamiaceae) and lemon balm (Melissa officinalis L., Lamiaceae) against the bean weevil Acanthoscelides obtectus (Say) adults under laboratory conditions. Volatile phase effects of different concentrations of the essential oils were used to determine insecticidal activities. Laboratory bioassay results indicated that all essential oils were found to cause 100 % adult mortality of A. obtectus in a dose-dependent manner. Essential oils of thyme and origanum had the highest insecticidal effects, causing high adult mortalities at the lower concentration (10 μg mL-1 air) in comparison to other essential oils tested. Adult viability was totally affected by essential oils of rosemary, basil and lemon balm at the concentrations of 20, 30 and 30 μg mL-1 air, respectively. The estimated LC50 (lethal concentration 50) values obtained for each essential oil were calculated by using probit analysis. The lowest LC50 values were recorded for thyme essential oil (1.12 μg mL-1) was followed by origanum (1.31 μg mL-1), rosemary (2.66 μg mL-1), basil (3.10 μg mL-1) and lemon balm (3.60 μg mL-1) respectively. The results of the present study concluded that plant essential oils could be useful in promoting research aiming at the development of new agent for pest control from the plants with medicinal values.